Double-edged sword: impact of fecal microbiome transplants on the gut resistome. Issue 1 (3rd January 2023) - Hallowell, Haley Anne; Gao, Anne Lulu; Suez, Jotham
Abstract : Purpose of review: Fecal microbiome transplants (FMT) show promise in treating various diseases, such as Clostridioides difficile infections. FMT have also demonstrated the capacity to modulate the collection of antibiotic resistance genes (ARGs), termed the resistome, within the gut. The purpose of this review was to critically evaluate the literature regarding the interaction between FMT and the gut resistome and determine whether FMT could be used specifically to reduce ARG carriage in the gut. Recent findings: Several studies have demonstrated a decrease in ARG carriage post-FMT administration in various disease states, including recurrent C. difficile infection and after antibiotic usage. However, other studies have reported an expansion of the resistome following FMT. Most studies contained small patient cohorts regardless of the outcome and showed heterogeneity in responses. Summary: Research on resistome modulation by FMT is preliminary, and human studies currently lack consensus regarding benefits and risks. From a safety perspective, screening donor samples for ARGs in addition to antibiotic-resistant organisms may be advisable. Additional studies on the mechanisms underlying heterogeneity between studies and individuals are required before FMT is considered an efficient approach for resistome amelioration.